Penerapan Sistem Absensi Fingerprint Dengan Menggunakan Visual Basic 6.0 di CV. MEDIA INOVASI - Denny Setyawan (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2018)
Attendance is important for an agency or company. because it is used in calculating the salary or wages of an employee and from absenteeism can also see the discipline of employee attendance. Therefore, in the implementation of the attendance process it is very necessary accuracy in its implementation so as not to hamper the company's performance.This final project designs an employee attendance system at CV. INNOVATION MEDIA that is useful to provide good absentee information quickly and easily, also through this study is expected to provide convenience to employees of CV. INNOVATION MEDIA in attendance. The design of employee attendance systems at CV. This INNOVATION MEDIA was developed using Visual Basic 6.0 software and with Finger Print as a tool. This system records employee attendance in the form of a daily attendance list. It is used to store data - data needed to expedite the information system.With this system the data processing is expected to be more effective and efficient. Even searching for data will be easier. The purpose of this research is to design an employee attendance information system that is expected to help the company's performance especially in the Human Resources Field to be faster and more practical.